I pianeti girano pure - Cousido, Jaime Palomo (Jaime Palomo Cousido, 2003)
Presents the short story of three people and their bikes. Anna, who is 29 years old is learning to ride a bike. Antonio, 77 years old has a bike shop in the center of Bologna, Italy. Leonardo, as a form of therapy, brings back to life the abandoned bicycles in the city.